2020
DOI: 10.1186/s12891-020-03622-6
|View full text |Cite
|
Sign up to set email alerts
|

Revision surgery for instrumentation failure after total en bloc spondylectomy: a retrospective case series

Abstract: Background: There have been several reports of instrumentation failure after three-column resections such as total en bloc spondylectomy (TES) for spinal tumors; however, clinical outcomes of revision surgery for instrumentation failure after TES are seldom reported. Therefore, this study assessed the clinical outcomes of revision surgery for instrumentation failure after TES. Methods: This study employed a retrospective case series in a single center and included 61 patients with spinal tumors who underwent T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…Nonetheless, several recent reports have presented results on mechanical failure after TES, such as screw loosening, screw back-out, cage breakage, screw fracture, and rod fracture; these studies identified rod fracture as the most common type of failure, and it often led to reoperation [ 8 , 11 , 12 , 22 , 23 ]. Shinmura et al [ 8 ] showed that instrumentation failure occurred in 43% of patients at a mean interval of 32 months (range, 11–92 months). Li et al [ 11 ] also showed that mechanical failure occurred in 27% (9 of 30) of patients at a mean interval of 32 months (range, 13–64 months).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, several recent reports have presented results on mechanical failure after TES, such as screw loosening, screw back-out, cage breakage, screw fracture, and rod fracture; these studies identified rod fracture as the most common type of failure, and it often led to reoperation [ 8 , 11 , 12 , 22 , 23 ]. Shinmura et al [ 8 ] showed that instrumentation failure occurred in 43% of patients at a mean interval of 32 months (range, 11–92 months). Li et al [ 11 ] also showed that mechanical failure occurred in 27% (9 of 30) of patients at a mean interval of 32 months (range, 13–64 months).…”
Section: Discussionmentioning
confidence: 99%
“…The causes of rod fracture varied, and radiotherapy and surgery at the lumbar spine were common causes [ 8 , 11 - 13 , 18 , 22 , 23 ]. Although wide resection is the goal of TES, preoperative or postoperative radiotherapy and/or chemotherapy may be necessary for better oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations